(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This review provides background knowledge of O. mossambicus conservation genetics studies and the invasive potential of O. niloticus. The detailed aspects of 1) the species biology, taxonomy, geographic distribution, beneficial traits, and its conservation status; (2) O. niloticus biology and invasive potential; and, (3) the threat posed by O. niloticus in South Africa. The O. mossambicus is a deep-bodied, yellowish or dull greenish colour with weak bands. An omnivorous fish of the genus Oreochromis, tribe Oreochromini that can weigh up to 1.1 kg and globally used for aquaclture. They are indigenous to south Africa that can thrive in fresh, brackish, and seawater, with valued traits of tolerance to salinity, cold temperatures and drought. They are classified as “Vulnerable” on the IUCN Red List because of hybridization with O. niloticus and need to be conserved. Oreochromis niloticus can attain approximately 60 cm (standard length), 4.3 kg in weight, and are often aggressive competitors that out-compete other species for spawning and breeding grounds if these are limited. These attributes inherently predisposed O. niloticus as an invasive species. Introduced into South Africa, for aquaculture and its escape from farms, leads to hybridization with native O. mossambicus. Most reports of hybridisation and introgression are from the Limpopo river system in northern South Africa with few data from other regions. Secondly, previous works do not reflect whole genome diversity with low comparability among nuclear DNA markers. This article suggested a SNP based molecular approach with robust sampling in assessing introgressive hybridization of O. niloticus into O. mossambicus in South Africa.